abd(7x-1)=abc(3x-9)

Simple and best practice solution for abd(7x-1)=abc(3x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for abd(7x-1)=abc(3x-9) equation:


Simplifying
abd(7x + -1) = abc(3x + -9)
Reorder the terms:
abd(-1 + 7x) = abc(3x + -9)
(-1 * abd + 7x * abd) = abc(3x + -9)
(-1abd + 7abdx) = abc(3x + -9)
Reorder the terms:
-1abd + 7abdx = abc(-9 + 3x)
-1abd + 7abdx = (-9 * abc + 3x * abc)
-1abd + 7abdx = (-9abc + 3abcx)
Solving
-1abd + 7abdx = -9abc + 3abcx
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '9abc' to each side of the equation.
-1abd + 9abc + 7abdx = -9abc + 9abc + 3abcx
Reorder the terms:
9abc + -1abd + 7abdx = -9abc + 9abc + 3abcx
Combine like terms: -9abc + 9abc = 0
9abc + -1abd + 7abdx = 0 + 3abcx
9abc + -1abd + 7abdx = 3abcx
Add '-3abcx' to each side of the equation.
9abc + -1abd + -3abcx + 7abdx = 3abcx + -3abcx
Reorder the terms:
9abc + -3abcx + -1abd + 7abdx = 3abcx + -3abcx
Combine like terms: 3abcx + -3abcx = 0
9abc + -3abcx + -1abd + 7abdx = 0
Factor out the Greatest Common Factor (GCF), 'ab'.
ab(9c + -3cx + -1d + 7dx) = 0

Subproblem 1

Set the factor 'ab' equal to zero and attempt to solve: Simplifying ab = 0 Solving ab = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ab = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(9c + -3cx + -1d + 7dx)' equal to zero and attempt to solve: Simplifying 9c + -3cx + -1d + 7dx = 0 Solving 9c + -3cx + -1d + 7dx = 0 Move all terms containing a to the left, all other terms to the right. Add '-9c' to each side of the equation. 9c + -3cx + -1d + -9c + 7dx = 0 + -9c Reorder the terms: 9c + -9c + -3cx + -1d + 7dx = 0 + -9c Combine like terms: 9c + -9c = 0 0 + -3cx + -1d + 7dx = 0 + -9c -3cx + -1d + 7dx = 0 + -9c Remove the zero: -3cx + -1d + 7dx = -9c Add '3cx' to each side of the equation. -3cx + -1d + 3cx + 7dx = -9c + 3cx Reorder the terms: -3cx + 3cx + -1d + 7dx = -9c + 3cx Combine like terms: -3cx + 3cx = 0 0 + -1d + 7dx = -9c + 3cx -1d + 7dx = -9c + 3cx Add 'd' to each side of the equation. -1d + d + 7dx = -9c + 3cx + d Combine like terms: -1d + d = 0 0 + 7dx = -9c + 3cx + d 7dx = -9c + 3cx + d Add '-7dx' to each side of the equation. 7dx + -7dx = -9c + 3cx + d + -7dx Combine like terms: 7dx + -7dx = 0 0 = -9c + 3cx + d + -7dx Simplifying 0 = -9c + 3cx + d + -7dx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| X+2/3=8/15 | | 56=x+x+5+2x-5 | | abd(7x-1)=abc(3x-9)findmabc | | y-(-2)=(-5/6)(x-3) | | 1/4-4 | | b+0.99=13.71 | | 2x^2-5=4.5 | | x+1/13=6/10 | | 21x-7-18x+3=17x-5-14x+16 | | (6w^3x+8w^5)/(8u^4w^4) | | 80(3.14)=2(3.14)5(5+h) | | 0.1(0.1x+0.5)=-.8 | | -7a+5=-10-29 | | 0.1(0.1x+0.5)=-.08 | | -x^2-5x+5=0 | | (4/5)(-3/8) | | -8v+6v=-7-3v | | Y-60=-10/7(x-10) | | 2x+4ab=3x-5ab | | 13(x+2)-4(x-2)=4(x-3)+4(x-4) | | r^2s^5t^4/r^2s^2t^5 | | y=-x^2-5x+5 | | 3x+5=9+3x | | 3(x+8)=8x+2-5x+22 | | a6/a2 | | 7/y^2-4-4/y+2=5/y-2 | | 5x/28-4=x/7+1 | | R^2=8-r^2 | | BAC=0.1 | | 4(4x-7)-2=4(x-4)+58 | | W=1.6t-54.6 | | 7x^2-5x=2 | | y-(-6)=(-7/8)(x-5) | | 3x^2-2x=-1 | | 8x^2-8x=16 | | 28a/4a | | 12(v+4)-4v=2(4v+1)-10 | | -7(v+4)+3v+7=5v+11 | | 1/6(7t-9)=(t+9)/12 | | 4[3-(-6x-6)]=168x+180 | | 12xy+1-6x-2y= | | -8=(x/2)-5 | | 2x+3=540 | | -9n-7=11 | | 3x^2+1=37 | | 12xy+16x-2y= | | 6(-4)-2(-1)+12= | | 6(1)-2(4)+12= | | 5x=(1/2)(16-8y) | | 3x+2y=468 | | 3x^2+7x-18=0 | | 3/8+(-1/8) | | 7a^2=3a | | x+8=4x+16 | | 10x-10=4x | | g(x)=x-2 | | 10x-1=4x | | y-(-7)=(-2/3)(x-7) | | -18x=96 | | y=-2x-y | | = | | g(x)=x+1 | | 2.1z=1.2z-8 | | w*5w+10=380 | | 2w-40*w=220 |


Related pages


2x 3y 6 graphis 196 a prime numberwhich equation is equivalent to 2x 6y 12derivative solver with stepsprime factorization of 99042-600cos 4x cos 3x sin 4x sin 3xwhat is 25 of 15gcf of 261975 in roman numeralsdecimals fractions20 thousand pounds in dollarsfactor completely 2x2 2x 12xxx 18sdivide fractions calculatorderivative of e lnx91.1xsin 2x cos 2x 089 prime factorizationprime factors of 275t182 calculatoralgebra factoring calculator with stepsy94 games2x squaredprime factorization of 123what is the prime factorization of 165yi7factor 2x 2-3x-2kx250.375 as a fraction7x 5 5xwhat is 16 percent as a decimalroman numerals 198851 prime factorizationesxy101010 in decimalderivative of x 2e xsolve 2x y 7percentages decimalshcf of 90 and 120differentiate ln 2x 3cosxsinxsimplify the square root of 150least to greatest decimals calculatormultiplying and dividing fractions calculatorwhat is the prime factorization for 6012345678910 123456789106x 3y 48g1what is the prime factorization of 650cos cosxderivative of cos3x140-111factor completely 2x2 2x 12lcm calculator0.875 in fraction2cosxcommon multiples of 15y 2cosxgraph 2x y 4fractions with letters calculatortimes fractions calculatorwhat is the prime factorization of 164x2 2x 15 05x squaredwhat is the greatest common factor of 28 and 42how to solve i prtcos2a0.083 as a fractionprime factorization of 432solving fraction calculator70-28roman numerals 1111prime factorization 198